2004
DOI: 10.1158/0008-5472.can-04-1454
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B but not Ultraviolet A Radiation Initiates Melanoma

Abstract: Cutaneous malignant melanoma is one of the fastest increasing cancers with an incidence that has more than doubled in the last 25 years. Sunlight exposure is strongly implicated in the etiology of cutaneous malignant melanoma and the UV portion of the sunlight spectrum is considered responsible. Data are, however, conflicting on the roles of ultraviolet B [UVB; 280 -320 nanometers (nm)] and ultraviolet A (UVA; 320 -400 nm), which differ in their ability to initiate DNA damage, cell signaling pathways and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
237
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(253 citation statements)
references
References 19 publications
13
237
0
3
Order By: Relevance
“…Ultraviolet B (UVB) is a well-known major risk factor for the development of acute inflammation as well as non-melanoma skin cancer in epidermis (De Fabo et al, 2004;Ramos et al, 2004). Accumulating data indicate that UVB exerts its detrimental effect mainly through the induction of direct DNA damage or the production of reactive oxygen species (ROS) (de Gruijl, 2002;Kulms et al, 2002;Heck et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet B (UVB) is a well-known major risk factor for the development of acute inflammation as well as non-melanoma skin cancer in epidermis (De Fabo et al, 2004;Ramos et al, 2004). Accumulating data indicate that UVB exerts its detrimental effect mainly through the induction of direct DNA damage or the production of reactive oxygen species (ROS) (de Gruijl, 2002;Kulms et al, 2002;Heck et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mammalian models, including the South American opossum (Monodelphis domestica) and several genetically modified mouse models, demonstrate that UVA does not induce melanomas (5)(6)(7). In contrast, evidence from all of these models, including Xiphophorus, supports a role for UVB in the etiology of melanoma.…”
mentioning
confidence: 99%
“…Hence epidemiological data is somewhat supportive of the view that the full UVR spectrum may be carcinogenic in melanoma. It should be noted that at any point on the earth it is difficult to precisely predict the UVA/UVB ratio in sunlight as it can greatly vary with time of day, altitude, latitude and climate factors (De Fabo et al, 2004).…”
Section: The Epidemiological Association Between Sunlight and Melanommentioning
confidence: 99%
“…Despite it being a somewhat specialized system, there is much we can learn using the neonatal UVR about how UVR results in melanocyte transformation. For instance using the Mt-Hgf model (with overexpression hepatocyte growth factor throughout the skin) it has been shown that UVB, and not UVA, induces melanoma (de Fabo et al, 2004), and that use of sunscreen can attenuate its development (Klug et al, 2010). The skin of hairless mice contains some epidermal melanocytes, hence the animals represent a murine system amenable to chronic UVR exposures.…”
Section: Modeling Chronic-induced Melanoma In Micementioning
confidence: 99%